ANALISIS SISTEM AKUNTANSI PENGGAJIAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA DAROY BANDA ACEH - Maksalmina Maksalmina (Jurnal Akuntansi Muhammadiyah (JAM), 2017)
This research was conducted at PDAM Tirta Daroy Banda Aceh, with the aim to answer the question of how the payroll accounting system applied in PDAM Tirta Daroy Banda Aceh.This research uses descriptive qualitative method. Data obtained from interviews and documentation studies, then analyzed interactively and lasted continuously until complete so that the data has been saturated. Activity in data analysis is data reduction, data presentation, treanggulation and conclusion / verification.The results show PDAM Tirta Daroy Banda Aceh has implemented a neat and well-payroll accounting system in accordance with applicable accounting standards. Payroll accounting system in PDAM Tirta Daroy Banda Aceh is used to overcome errors and irregularities in the calculation and payment of salary. Payroll accounting systems are designed by companies to provide a clear picture of employee salaries so that they are easy to understand and easy to use.